Burden of influenza among hospitalized febrile children in Ghana. Issue 6 (27th October 2017) - Hogan, Benedikt; Ammer, Luise; Zimmermann, Marlow; Binger, Tabea; Krumkamp, Ralf; Sarpong, Nimako; Rettig, Theresa; Dekker, Denise; Kreuels, Benno; Reigl, Lisa; Boahen, Kennedy G.; Wiafe, Charity; et al.
Abstract : Background: Influenza surveillance data from Africa indicate a substantial disease burden with high mortality. However, local influenza data from district hospitals with limited laboratory facilities are still scarce. Objectives: To identify the frequency and seasonal distribution of influenza among hospitalized febrile children in a rural hospital in Ghana and to describe differential diagnoses to other severe febrile infections. Methods: Between January 2014 and April 2015, all children with a temperature of ≥38°C admitted to a district hospital in Ghana were screened for influenza A and B by RT‐PCR and differentiated to subtypes A(H1N1)pdm09 and A(H3N2). Malaria microscopy and blood cultures were performed for each patient. Results: A total of 1063 children with a median age of 2 years (IQR: 1‐4 years) were recruited. Of those, 271 (21%) were classified as severe acute respiratory infection (SARI) and 47 (4%) were positive for influenza, namely 26 (55%) influenza B, 15 (32%) A(H1N1)pdm09, and 6 (13%) A(H3N2) cases. Influenza predominantly occurred in children aged 3‐5 years and was more frequently detected in the major rainy season (OR = 2.9; 95% CI: 1.47‐6.19) during the first half of the year. Two (4%) and seven (15%) influenza‐positive children were co‐diagnosed with an invasive bloodstream infection or malaria, respectively. Conclusion: Influenza contributes substantially to the burden of hospitalized febrile children in Ghana being strongly dependent on age and corresponds with the major rainy season during the first half‐year.